2022
DOI: 10.3389/fmicb.2022.914472
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Utilization and Competitive Interactions Among Soil Bacteria Vary With Life-History Strategies

Abstract: Microorganisms have evolved various life-history strategies to survive fluctuating resource conditions in soils. However, it remains elusive how the life-history strategies of microorganisms influence their processing of organic carbon, which may affect microbial interactions and carbon cycling in soils. Here, we characterized the genomic traits, exometabolite profiles, and interactions of soil bacteria representing copiotrophic and oligotrophic strategists. Isolates were selected based on differences in ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…5A) . This is consistent with a recent study that showed that coumaric acid is generally not a preferred microbial substrate by soil bacterial isolates in vitro ( 49 ). Our data suggest that concentrations of 500 µM and higher can have phytotoxic activity on Brachypodium seedlings and may negatively impact crop productivity ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…5A) . This is consistent with a recent study that showed that coumaric acid is generally not a preferred microbial substrate by soil bacterial isolates in vitro ( 49 ). Our data suggest that concentrations of 500 µM and higher can have phytotoxic activity on Brachypodium seedlings and may negatively impact crop productivity ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Within these, only the order Micrococcales had a significantly higher relative abundance in LNA bacteria. Their isolates had the potential to compete with others for substrates (Wang, Wilhelm, et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, for senescing roots that have ceased exudation, microbial investment in extracellular polymer breakdown will further increase resource-based niche partitioning [42]. Further, positive interactions between rhizosphere bacteria may contribute to a more efficient microbial stabilization route via cross-feeding of metabolic byproducts [67], although the stability of microbially-derived carbon is likely impacted by the mechanism and kinetics of microbial mortality [60].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their metabolic diversity, bacteria with larger genomes may be more ecologically successful where resources are scarce but diverse, and where there is little penalty for slow growth [13]. In contrast, bacteria found to be resource generalists in culture have higher rRNA copy numbers, indicative of copiotroph lifestyles, than bacteria with low rRNA copy numbers that were associated with a higher degree of specialization [67]. These mixed results question whether evolutionary trade-offs between power and yield can be generalized from genomes alone.…”
Section: Discussionmentioning
confidence: 99%